Digital Marketing Approaches For Tourism Growth: A Study of Puncak Bila, Sidrap - Muhammad Danyal; Titien Damayanti; Hanugerah Kristiono Liestiandre (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study explores the effectiveness of digital marketing strategies in increasing tourist visits to Puncak Bila Tourism Park, Sidrap, South Sulawesi. Employing a qualitative descriptive approach through interviews, observations, and documentation, the research examines supporting and constraining factors in digital promotion. Results indicate that social media platforms Instagram, TikTok, and Facebook play a central role in destination branding, strengthened by user-generated content (UGC) that broadens reach organically. Visitor data from 2021 to 2024 show a sharp rise in arrivals, reflecting the positive impact of digital promotion. However, constraints remain, including limited digital skills, insufficient infrastructure, and weak SME integration. To address these gaps, strategic solutions based on the Penta Helix model capacity building, website development, and cross-sector collaboration are recommended. This study enriches theoretical perspectives on destination marketing while providing practical implications for sustainable, community-based tourism development in Indonesia.